Assessment of the efficacy of olopatadine 0.1% in the treatment of vernal keratoconjunctivitis in terms of clinical improvement based on total ocular symptom score and ocular surface disease index - S Mohan; Santosh Kumar; G Pawan Kumar; Anjali Maheswari; Agrima Bhatia; Anand Sagar (Indian Journal of Ophthalmology, 2023)
Purpose: The main objective of this study is to explore the efficacy of olopatadine 0.1% treatment in the resolution of symptoms of vernal keratoconjunctivitis (VKC) among the Indian population. Methods: This single-center, prospective cohort study involved 234 patients with VKC. Patients were treated with olopatadine 0.1%, twice daily for a period of 12 weeks and then followed up in 1st week, 4th week, 3rd month, and 6th month. The extent of relief in the symptoms of VKC was measured using total ocular symptom score (TOSS) and ocular surface disease index (OSDI). Results: In the present study, the dropout rate was 5.6%. Total of 136 males and 85 females with a mean age of 37.68 ± 11.35 years completed the study. TOSS score reduced from 58.85 to 5.06 and the OSDI score reduced from 75.41 to 11.2 with statistical significance (P < 0.01) from 1st week to 6th week after olopatadine 0.1% treatment. The data showed relief in subjective symptoms of itching, tearing, and redness, and relief in discomfort in functions related to ocular grittiness, visuals like reading, and environmental like tolerability in dry conditions. Further, olopatadine 0.1% was effective in both males and females, and patients across ages 18–70 years. Conclusion: Based on TOSS and OSDI scores, the findings of this study validate safety and tolerability as revealed by low adverse effects and moderate efficacy of olopatadine 0.1% in reducing VKC symptoms in a broader age group (18–70 years) of both genders.